One Painting, Two Emperors, and Their Cultural Agendas: Reinterpreting the Qingming Shanghe Painting of 1737 - Wang, Cheng-hua (Archives of Asian art)
This research focuses on one of the most famous paintings made at the court of the Qing dynasty (1644–1911)— (Up the River during Qingming). Commissioned by the Yongzheng emperor (r. 1723–1735) and completed in the second year of the Qianlong emperor's reign (1736–1795), the painting is a rare example of Qing court art that reveals how Qianlong furthered his father's artistic vision while formulating his own in the first fifteen years of his long tenure as ruler. This vision involved how to reinterpret and reinvent the Chinese painting tradition through time-honored themes. The article is divided into four sections. In the first, it brings attention to the salient and crucial but long neglected stylistic features of the painting—those that emphasize theatricality and spectatorship. These interconnected features link and characterize the paintings commissioned by Yongzheng. The second section shifts to discuss the emerging cultural agenda of Yongzheng as seen through the manner in which court art references the Chinese painting tradition. The most remarkable act regards the reinterpretation of old painting themes that include and (One Hundred Horses). The third section analyzes how the paratextual elements of , especially Qianlong's poem and inscription, inform us of the emperor's views about the production mechanism of court painting and the political meaning of this work. The last section, based on Qianlong's understanding of the painting, highlights the emperor's cultural agenda associated with the idea of , which pointed to new versions of old themes made by his painting academy.